COLOR SCHEME IN THE FORMATION OF THE ARTISTIC ENVIRONMENT OF THE INTERIOR OF MODERN EDUCATIONAL CENTERS - Sultonova , Dilshoda Namazovna; Siddiqova , Madinabonu Asatilla qizi (Educational Research in Universal Sciences, 2023)
In this article, the role and importance of colors in the artistic design of educational institutions and educational centers is studied. Scientific solutions for the design of color types, taking into account the type of educational institution and the psychophysiological abilities of students, are presented by the authors. studied.